Molecular epidemiology and drug sensitivity of Mycobacterium tuberculosis in homeless individuals in the Addis Ababa city, Ethiopia - Tsegaye Shamebo; Balako Gumi; Aboma Zewude; Fikru Gashaw; Temesgen Mohammed; Muse Girma; Betselot Zerihun; Melak Getu; Sindew Mekasha; Muluwork Getahun; Biniam Wondale; Beyene Petros; et al. (Scientific Reports, 2023)
Abstract Although homeless segment of the society could be the hotspots for tuberculosis (TB) transmission, there is little data on TB in homeless individuals in Ethiopia. The objective of this study was to investigate the molecular epidemiology and drug sensitivity of Mycobacterium tuberculosis (M. tuberculosis) isolated from homeless individuals in Addis Ababa, Ethiopia. The study was conducted on 59 M. tuberculosis isolates, which were recovered by the clinical screening of 5600 homeless individuals and bacteriological examination of 641 individuals with symptoms of pulmonary tuberculosis (PTB). Region of difference-9 (RD9) based polymerase-chain reaction (PCR), Spoligotyping and 24-loci Mycobacterial Interspersed Repetitive Unit-Variable Number Tandem Repeat (MIRU-VNTR) typing were used for genotyping of the isolates. In addition, drug sensitivity test was performed on the isolates using BD Bactec Mycobacterial Growth Inhibition Tube (MGIT) 960. Fifty-eight of the 59 isolates were positive by spoligotyping and spoligotyping International type (SIT) 53, SIT 37, and SIT 149 were the dominant spoligotypes; each consisting of 19%, 15.5%, and10.3% of the isolates, respectively. The majority of the isolates (89.7%) were members of the Euro-American (EA) major lineage. MIRU-VNTR identified Ethiopia_3, Delhi/CAS, Ethiopia_2, TUR, X-type, Ethiopia_H37Rv-like strain, Haarlem and Latin-American Mediterranean (LAM) sub lineages. The proportion of clustering was 77.6% (45/58) in spoligotyping while it was 39.7% (23/58) in 24-loci MIRU-VNTR typing. Furthermore, the proportion of clustering was significantly lowered to 10.3% (6/58) when a combination of spoligotyping and 24-loci MIRU-VNTRplus was used. The recent transmission index (RTI) recorded by spoligotyping, 24-loci MIRU-VNTR typing, and a combination of the two genotyping methods were 58.6%, 27.6% and 5.2%, respectively. Young age and living in groups were significantly associated with strain clustering (P < 0.05). The drug sensitivity test (DST) result showed 8.9% (4/58) of the isolates were resistant to one or more first line ant-TB drugs; but multidrug resistant isolate was not detected. Clustering and RTI could suggest the transmission of TB in the homeless individuals, which could suggest a similar pattern of transmission between homeless individuals and the general population. Hence, the TB control program should consider homeless individuals during the implementation of TB control program.